Ergoline‐Derived Inverse Agonists of the Human H3 Receptor for the Treatment of Narcolepsy. Issue 8 (21st May 2014) - Auberson, Yves P.; Troxler, Thomas; Zhang, Xuechun; Yang, Charles R.; Fendt, Markus; Feuerbach, Dominik; Liu, Yu‐Chih; Lagu, Bharat; Lerchner, Andreas; Perrone, Mark; Lei, Lijun; Zhang, Chao; et al.
Abstract Ergoline derivative (6aR, 9R)‐4‐(2‐(dimethylamino)ethyl)‐N‐phenyl‐9‐(pyrrolidine‐1‐carbonyl)‐6, 6a, 8, 9‐tetrahydroindolo[4, 3‐fg]quinoline‐7(4H)‐carboxamide (1), a CXCR3 antagonist, also inhibits human histamine H3 receptors (H3R) and represents a structurally novel H3R inverse agonist chemotype. It displays favorable pharmacokinetic and in vitro safety profiles, and served as a lead compound in a program to explore ergoline derivatives as potential drug candidates for the treatment of narcolepsy. A key objective of this work was to enhance the safety and efficacy profiles of 1, while minimizing its duration of action to mitigate the episodes of insomnia documented with previously reported clinical candidates during the night following administration. Modifications to the ergoline core at positions 1, 6 and 8 were systematically investigated, and derivative 23 (1‐((4aR, 8R, 9aR)‐8‐(hydroxymethyl)‐1‐(2‐((R)‐2‐methylpyrrolidin‐1‐yl)ethyl)‐4, 4a, 7, 8, 9, 9a‐hexahydroindolo[1, 14‐fg]quinolin‐6(1H)‐yl)ethanone) was identified as a promising lead compound. Derivative 23 has a desirable pharmacokinetic profile and demonstrated efficacy by enhancing brain concentrations of tele‐methylhistamine, a major histamine metabolite. This validates the potential of the ergoline scaffold to serve as a template for the development of H3R inverse agonists.